Collusive vertical relations - Stefano Bolatto; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
We investigate the possibility for two vertically related firms to at least partially collude on the wholesale price over an in.nite horizon to mitigate or eliminate the e¤ects of double marginalisation, thereby avoiding contracts which might not be enforceable. We characterise alternative scenarios envisaging different deviations by the upstream firm and different punishments. This allows us to show that the most efficient case is that in which the upstream firm deviates along its best reply function and the punishment prescribes the disruption of the vertical relation for good after a deviation from the collusive path.
Keywords: D43; L13; L42; 330; collusion; double marginalisation; supply chain; vertical integration